Yolk sac erythromyeloid progenitors expressing gain of function PTPN11 have functional features of JMML but are not sufficient to cause disease in mice. Issue 12 (23rd October 2017) - Tarnawsky, Stefan P.; Yoshimoto, Momoko; Deng, Lisa; Chan, Rebecca J.; Yoder, Mervin C.
Abstract : Background : Accumulating evidence suggests the origin of juvenile myelomonocytic leukemia (JMML) is closely associated with fetal development. Nevertheless, the contribution of embryonic progenitors to JMML pathogenesis remains unexplored. We hypothesized that expression of JMML‐initiating PTPN11 mutations in HSC‐independent yolk sac erythromyeloid progenitors (YS EMPs) would result in a mouse model of pediatric myeloproliferative neoplasm (MPN).Results : E9.5 YS EMPs from VavCre+;PTPN11 D61Y embryos demonstrated growth hypersensitivity to granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) and hyperactive RAS‐ERK signaling. Mutant EMPs engrafted the spleens of neonatal recipients, but did not cause disease. To assess MPN development during unperturbed hematopoiesis we generated CSF1R‐MCM+;PTPN11 E76K ;ROSA YFP mice in which oncogene expression was restricted to EMPs. Yellow fluorescent protein‐positive progeny of mutant EMPs persisted in tissues one year after birth and demonstrated hyperactive RAS‐ERK signaling. Nevertheless, these mice had normal survival and did not demonstrate features of MPN.Conclusions : YS EMPs expressing mutant PTPN11 demonstrate functional and molecular features of JMML but do not cause disease following transplantation nor following unperturbed development. Developmental Dynamics 246:1001–1014, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Are hypersensitive to GM‐CSF and possess hyperactive RAS‐ERK signaling. Give rise to long‐lived splenic macrophages upon transplantation into neonatal recipients. Do not cause myeloproliferative disease in a mouse model following in utero oncogene expression with CSF1R Mer‐Cre‐Mer.